Coenzyme Q10 as a potent compound that inhibits Cdt1–geminin interaction - Mizushina, Yoshiyuki; Takeuchi, Toshifumi; Takakusagi, Yoichi; Yonezawa, Yuko; Mizuno, Takeshi; Yanagi, Ken-ichiro; Imamoto, Naoko; Sugawara, Fumio; Sakaguchi, Kengo; Yoshida, Hiromi; Fujita, Masatoshi (Biochimica et biophysica acta, 2008)
A human replication initiation protein Cdt1 is a very central player in the cell cycle regulation of DNA replication, and geminin down-regulates Cdt1 function by directly binding to it. It has been demonstrated that Cdt1 hyperfunction resulting from Cdt1–geminin imbalance, for example by geminin silencing with siRNA, induces DNA re-replication and eventual cell death in some cancer-derived cell lines. In the present study, we first established a high throughput screening system based on modified ELISA (enzyme linked immunosorbent assay) to identify compounds that interfere with human Cdt1–geminin binding. Using this system, we found that coenzyme Q10 (CoQ10) can inhibit Cdt1–geminin interaction in vitro. CoQ compound is an isoprenoid quinine that functions as an electron carrier in the mitochondrial respiratory chain in eukaryotes. CoQ10, having a longer isoprenoid chain, was the strongest inhibitor of Cdt1–geminin binding in the tested CoQs, with 50% inhibition observed at concentrations of 16.2 μM. Surface plasmon resonance analysis demonstrated that CoQ10 bound selectively to Cdt1, but did not interact with geminin. Moreover, CoQ10 had no influence on the interaction between Cdt1 and mini-chromosome maintenance (MCM)4/6/7 complexes. These results suggested that CoQ10 inhibits Cdt1–geminin complex formation by binding to Cdt1 and thereby could liberate Cdt1 from inhibition by geminin. Using three-dimensional computer modeling analysis, CoQ10 was considered to interact with the geminin interaction interface on Cdt1, and was assumed to make hydrogen bonds with the residue of Arg243 of Cdt1. CoQ10 could prevent the growth of human cancer cells, although only at high concentrations, and it remains unclear whether such an inhibitory effect is associated with the interference with Cdt1–geminin binding. The application of inhibitors for the formation of Cdt1–geminin complex is discussed.